Individual- and Community-Level Factors Associated with Diarrhea in Children Younger Than Age 5 Years in Bangladesh: Evidence from the 2014 Bangladesh Demographic and Health Survey - Md Moustafa Kamal; Tilahun Tewabe, MSc; Tsheten Tsheten, MPH; Syeda Z. Hossain, PhD (Elsevier, 2022)
ABSTRACT: Background: Diarrheal disease is among the leading causes of morbidity and mortality among children younger than age 5 years in Bangladesh. Objective: The objective of this study is to assess the prevalence of diarrhea among children younger than age 5 years and its associated risk factors. Methods: Data were sourced from the Bangladesh Demographic and Health Survey, a nationally representative study conducted in 2014. We used multilevel logistic regression models to identify factors associated with diarrheal disease. Results: Children aged 6 to11 months (odds ratio = 2.26; 95% CI, 1.50-3.42), and 12 to 23 months (odds ratio = 2.31; 95% CI, 1.62-3.31) were more likely to have diarrhea than older children. Other significant risk factors for diarrheal infection included households without access to drinking water (odds ratio = 1.39; 95% CI, 1.03-1.88) and mothers lacking mass media access (odds ratio = 1.32; 55% CI, 1.01-1.73). Conclusions: Childhood diarrhea in Bangladesh was associated with individual- and community-level factors. The finding of this study suggests that diarrhea prevention programs in the country can effectively be delivered by targeting young children through expanding community-based education and increasing access to health information through mass media.